Pride of the Marines - Waxman, Franz 1906-1967 (Distributed by Warner Home Video, 2010)
Based on the true story of a Marine blinded in the Battle of Guadalcanal during World War II. The story deals with the anger and fear he must confront once he returns home to civilian life and a world of darkness
Original: USA 1945
s/w, Bildformat: 4:3 (1.33:)
Keywords: Schmid, Al / (Albert) / Drama; United States / Marine Corps / Drama; Butterfield, Roger / 1907-1981 / Film adaptations; Schmid, Al / (Albert); United States / Marine Corps; Guadalcanal, Battle of (Solomon Islands : 1942-1943); Disabled veterans / Pennsylvania / Philadelphia / Biography / Drama; Guadalcanal, Battle of, Solomon Islands, 1942-1943 / Drama; Disabled veterans; Pennsylvania / Philadelphia; Solomon Islands; 1942-1943; Feature films / United States; Feature films; Biographical films; War films; Fiction films; Film adaptations; Drama; Film; DVD-Video